Synthesis of novel aza-heterocyclic derivatives from diester and diacid chlorides having the dibenzobarrelene skeleton - Capan, Irfan; Servi, Suleyman (Taylor & Francis Inc, 2018)
When attempting to synthesize the symmetric aza-heterocyclic-substituted dibenzobarrelene derivatives from the 2-aminobenzimidazole (or 2-aminoimidazoline) with diacid chlorides and diester in the presence of various organic bases, different products were isolated in high yield. NMR spectroscopic analysis proved these products to be dibenzobarrelene-substituted fused benzimidazodiazepine, imidazolinediazepine, and dicarboxamides derivatives. Cyclic or noncyclic dicarboxamides with the dibenzobarrelene skeleton have been synthesized for the first time using these methods. [GRAPHICS] .
Keywords: Benzimidazolediazepine; dibenzobarrelene; dicarboxamides; guanidine; imidazolinediazepine